(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to find out the percentage of future thinking skills in the content of the fourth grade mathematics book approved for teaching for the academic year (2021-2022 AD). For the curricula for the academic year (2021-2022 AD), a content analysis tool was prepared for this purpose according to the skills of future thinking, and its validity was verified by presenting it to a number of arbitrators in the field of curricula and methods of teaching mathematics, and the idea unit (explicit and implicit) was adopted as a unit for registration and repetition as a unit for enumeration. The validity of the analysis was confirmed by presenting a random sample of the analysis to a group of arbitrators, and frequencies, percentages, and the (Holisti) equation were used to calculate the stability of the analysis between the researcher and herself over time, and between her and other analysts. The research concluded that the skills of future thinking were all available in (low) rates (very-low), so the acting skill was (33.22%), the visualization skill was (25.68%), the problem-solving skill was (20.75%), and the prediction skill was (20.35%), respectively. In light of that, a number of recommendations were presented, including The need for the directorates of numbers and training to hold training courses, seminars and workshops for mathematics teachers at the primary stage in order to raise their professional levels and introduce them to the skills of future thinking, and train them to employ the skills of future thinking in their lessons. Future thinking skills.Keywords: content analysis, mathematics book for the fourth grade of primary school, future thinking skills.